Formulaic Sequences as Fluency Devices in the Oral Production of Native Speakers of Polish - Guz, Ewa (Research in Language, 2014)
In this paper we attempt to determine the nature and strength of the relationship between the use of formulaic sequences and productive fluency of native speakers of Polish. In particular, we seek to validate the claim that speech characterized by a higher incidence of formulaic sequences is produced more rapidly and with fewer hesitation phenomena. The analysis is based on monologic speeches delivered by 45 speakers of L1 Polish. The data include both the recordings and their transcriptions annotated for a number of objective fluency measures. In the first part of the study the total of formulaic sequences is established for each sample. This is followed by determining a set of temporal measures of the speakers' output (speech rate, articulation rate, mean length of runs, mean length of pauses, phonation time ratio). The study provides some preliminary evidence of the fluency-enhancing role of formulaic language. Our results show that the use of formulaic sequences is positively and significantly correlated with speech rate, mean length of runs and phonation time ratio. This suggests that a higher concentration of formulaic material in output is associated with faster speed of speech, longer stretches of speech between pauses and an increased amount of time filled with speech.